The Supplementation of Urea Molasses Multi-nutrient Moringa Block (UM3B) on the Diameter and Total Follicle in Balinese Cows - Abdul Malik; Siti Erlina; Aam Gunawan; Neni Widaningsih; Rizkie Elvania; Mawardi Mawardi (UNIVERSITAS ISLAM LAMONGAN, 2021)
The research of the aim to analyze giving of urea molasses multi-nutrient moringa block (UM3B) to the amount and diameter of follicles in crossbred cattle. A total of 10 cows were used study. all cows were divided two groups, one group consist of 5 crossbreed cows. Group one was given UM3B, and group two was not given UM3B (control). The result of this study about total of follicle was significant different (P > 0,05) between group one (with UM3B) and group two (control) without UM3B, whereas, the diameters of the follicles was no significant different (P <0,05) among group one with UM3B and group two without UM3B, but trend of diameter of follicle show batter with group one. The conclusion of study was the use of urea molasses multi-nutrient moringa block (UM3B) giving a positive impact on total of follicular growth in the right and left ovary.